Internal transcribed spacer metagenomics data unravelling the core fungal community structure residing the wheat and maize rhizosphereNCBINCBINCBI - Sadia Latif; Rizwana Kousar; Anum Fatima; Naeem Khan; Hina Fatimah (Data in Brief)
Plants are colonized by a vast array of microorganisms that outstrip plant cell densities and genes, thus referred to as plant's second genome or extended genome. The microbial communities exert a significant influence on the vigor, growth, development and productivity of plants by supporting nutrient acquisition, organic matter decomposition and tolerance against biotic and abiotic stresses such as heat, high salt, drought and disease, by regulating plant defense responses. The rhizosphere is a complex micro-ecological zone in the direct vicinity of plant roots and is considered a hotspot of microbial diversity. The exploration and understanding of the rhizosphere microbes can be valuable in sustainable agriculture. The present dataset aimed to reveal the core fungal community residing in the rhizosphere of wheat (Triticum aestivum L.) and maize (Zea mays L.). The rhizosphere fungal communities were explored via amplicon sequencing of the Internal Transcribed Spacer (ITS) region using the IonS5TMXL sequencing platform. The data obtained were filtered and the high-quality reads were clustered into Microbial Operational Taxonomic Units (OTUs) at 97 % similarity. Further, the data were subjected to alpha and beta diversity analysis. The OTUs obtained from the wheat rhizosphere soils of Kallar Syedian (TA.KS), Islamabad (TA.ISB) and Mirpur Azad Kashmir (TA.MAK) were 603, 513 and 424, respectively, whereas 616 OTUs were found in the maize rhizosphere soil of Kallar Syedian (ZM.KS). The major fungal phyla inhabiting the rhizosphere soils were Ascomycota, accounting for 94 %, 97 %, 95 % and 90 % of the fungal community in ZM.KS, TA.KS, TA.MAK and TA.ISB, respectively. Alpha and beta diversity analysis depicted the presence of considerable variations in the relative abundance of fungal groups residing in the rhizosphere soils. The dataset obtained can be employed in meta-analysis studies that will pave the way toward understanding the core fungal community structure and will directly aid in enhancing crop productivity through rhizosphere engineering.